PENGARUH STORE ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN INDOGROSIR KENDARI - Haris Khoirul Imam Khoirul Imam; Sudirman Zaid; Nofal Nur; Muhamad Masri; Riski Amalia Madi (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to determine both simultaneously and partially from store atmosphere and service quality on customer loyalty at Indogrosir Kendari. The population in this study are customers who make transaction at Indogrosir Kendari whose number is unknown. The sample of this research is 65 respondents with accidental or convenience sampling technique. The data collection mrthod in this study used a questionnaire. this study uses multiple linear regression analysis. The results showed that both simultaneously ans partially store atmosphere and service quality had a positive and significant effect on indogrosir kendari customer loyalty. Which means that if the store atmosphere and service quality are good, it will tend to effect customer loyalty.